HIV/AIDS and Mental Health - Baingana, Florence (World Bank, Washington, DC, 2013)
Mental and neurological disorders have an intertwined relationship with HIV, yet are often overlooked when AIDS interventions are planned and implemented. Cognitive disorders, substance abuse, and disorders of personality can influence behavior in ways that lead to greater risk of HIV infection. Conversely, HIV/AIDS itself can lead to psychological conditions due to circumstances surrounding the disease, and psychiatric conditions resulting from HIV-related neurological changes. Such disorders can adversely influence the progression of the disease, lead to noncompliance with prescribed medical treatment, and increase the likelihood that people living with HIV/AIDS (PLWHA) will act in high-risk ways. Since the World Bank is the largest long-term investor in the prevention and mitigation of HIV/AIDS in developing countries, it has an important role to play in mental health interventions related to the HIV/AIDS pandemic. The main purpose of this document is to increase knowledge of the relationship between HIV/AIDS and mental health and highlight the need for psychosocial support for PLWHA. The document begins with a description of the global AIDS pandemic, addresses psychosocial risks for infection, then discusses the socio-economic impact of HIV/AIDS. This is followed by a description of the neuro-psychiatric and psychological disorders associated with HIV/AIDS and the social and economic implications of failing to address these disorders. Next, current World Bank AIDS initiatives are considered, and opportunities and challenges for including mental health and psychosocial interventions in AIDS programming are explored. The document concludes with recommendations for future initiatives aimed at meeting the mental health and psychosocial needs of PLWHA.